2006
DOI: 10.1002/qsar.200610069
|View full text |Cite
|
Sign up to set email alerts
|

Towards Unified Compound Screening Strategies: A Critical Evaluation of Error Sources in Experimental and Virtual High‐Throughput Screening

Abstract: This contribution focuses on an assessment of errors in experimental and virtual screening. Sources of errors in high-throughput screening can be classified as logistic, measurement-related, or strategic. Biological assays formatted for high throughput are generally susceptible to small but systematic errors arising from a variety of sources, and the correction of such errors often requires the application of advanced data analysis methods. For virtual screening, chemical space design and molecular similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 60 publications
0
9
0
2
Order By: Relevance
“…Studies have demonstrated that models built on a structurally similar set of compounds occupying closely adjacent areas of chemical space are likely to have limited applicability in terms of identifying novel inhibitor classes, and thus may result in unreliable predictions when used in virtual screening of structurally diverse chemical databases. [34, 35]…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that models built on a structurally similar set of compounds occupying closely adjacent areas of chemical space are likely to have limited applicability in terms of identifying novel inhibitor classes, and thus may result in unreliable predictions when used in virtual screening of structurally diverse chemical databases. [34, 35]…”
Section: Introductionmentioning
confidence: 99%
“…Although each has its own distinct advantages, these methods share a common goal in that they both aim to identify a small number of true biological positives amidst a vast amount of biological negatives. [4, 5] …”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Some of these efforts have been facilitated by the use of such virtual screening (VS) tools as ligand-based QSAR, [9][10][11][12][13] 3D-QSAR, [14][15][16][17][18][19] and pharmacophore, [20] and structure-based molecular docking. [21][22][23][24][25][26] The applicability domains of these ligand-based methods in some cases are restricted [27,28] by limited diversity (< 200 compounds in most cases) [29][30][31] or structural types (e.g. hydroxamic acid derivatives only) in training dataset.…”
Section: Introductionmentioning
confidence: 99%